10.3928/08910162-20080701-01 (CrossRef Listing of Deleted DOIs, 2000)
Background Nursing education has long relied on rigid, protocol-driven teaching methods rooted in dominant historical models that emphasize memorization over meaningful understanding. These approaches no longer meet the demands of today's health care environment, where nurses must demonstrate critical thinking, creativity, and cultural responsiveness, autonomy, and advocacy. This review sought to synthesize evidence-informed pedagogical approaches that intentionally integrate both divergent thinking and convergent thinking into nursing education. Method A rapid review was conducted using CINAHL and PubMed databases to identify articles on pedagogies that elevate diverse student voices, foster independent critical and creative thinking, and promote advocacy. Relevant sources meeting predetermined inclusion criteria were reviewed. Results Twenty sources were reviewed. Findings show that students develop stronger critical thinking and clinical reasoning skills when learning moves beyond memorization and incorporates complex, socially grounded experiences. Conclusion Purposeful use of divergent thinking pedagogies produce independent nurse thinkers, leaders, and advocates necessary for today's health care.